Ondersoek na "n Johannese kerk/ skool: Metodologiese kantaantekeninge oor die verloop van die ondersoek - Lombard, H. A. (Hervormde teologiese studies, 1989)
Investigation of a Johannine church/school: Methodological remarks on the course of the case.In an effort to resolve a major facet of the ‘Johannine problem’ scholars assign the distinctiveness of the fourth gospel to its formation allegedly within and for a separate and independent Johannine community (or school). The reconstructions and descriptions of this community are presently assessed by critical scrutiny of the hermeneutical paradigms and exegetical procedures utilized by scholars. So, as is mostly the case within current New Testament science, this debate culminated in controversies on methodology.Opting for real progress and positive results, means that some or other integration/correlation of methods is inevitable. Proper and mutual cognisance must be taken of the vantage points and hermeneutical perceptions with which scholars work. This entails cooperative interaction between all forms of historical exegesis on the one hand, and text immanent exegesis on the other hand.